ChemInform Abstract: Metal Oxide/Hydroxide‐Based Materials for Supercapacitors. Issue 50 (16th December 2014) - Shi, Fan; Li, Lu; Wang, Xiu‐li; Gu, Chang‐dong; Tu, Jiang‐ping
Abstract Review: 207 refs.